Assessing Magnesium Chloride as a Chemical for Immobilization of a Symbiotic Jellyfish (Cassiopea sp.) - Arossa, Silvia; Klein, Shannon G.; Parry, Anieka J.; Aranda, Manuel; Duarte, Carlos M. (Frontiers in Marine Science, 2022)
Immobilization of marine invertebrates for research purposes has been commonly used and is often necessary to obtain high-quality findings. Despite these approaches being standard procedures, they can affect the specimens, and their responses as well. The effectiveness of magnesium chloride (MgCl2) to “narcotize” marine invertebrates has been recognized since 1942. Here, we determine the concentration of MgCl2 that immobilizes Cassiopea sp. individuals effectively and quickly, without causing mortality. The specimens were exposed to different concentrations of MgCl2, until the range was narrowed, and the most effective concentration was found (0.092M). In the final experiment, the jellyfish (~ 8.68 cm ± 1.70 SD of diameter) were exposed to a 0.092M MgCl2 solution for 2 and 24 hours. Before, during, and after the exposure we monitored the following biological responses: (1) cessation of bell pulsations, (2) responsiveness to bell-tap stimulus, (3) photochemical efficiency, (4) bell pulsation, (5) recovery time, and (6) survival after 24 and 48 hours from exposure. Environmental conditions (pH and dO2) were monitored as well. Our findings indicate that, despite being an effective concentration for immobilization of Cassiopea sp., their bell pulsations were significantly affected both after 2 and 24 hours when comparing the values measured in the “pre-incubation” and “immediate post-incubation” phases, whereas bell size was significantly affected only in the 24 hours incubation. In conclusion, we suggest that this concentration can be used to immobilize Cassiopea sp. specimens for short-term analyses. However, the limitations related to the use of this chemical should be reported, as it could lead scientists to misleading conclusions.